Identification of a Novel Ceftazidime-Avibactam-Resistant KPC-2 Variant, KPC-123, in Citrobacter koseri Following Ceftazidime-Avibactam Treatment - Wang, Lin; Shen, Weiyi; Zhang, Rong; Cai, Jiachang (Frontiers in Microbiology, 2022)
This study reported the identification of a novel ceftazidime-avibactam-resistant KPC-2 variant, KPC-123, in a Citrobacter koseri isolated from a patent in a Chinese hospital following ceftazidime-avibactam treatment of infection caused by OXA-232-producing Klebsiella pneumoniae. This novel KPC-123 consisting of 302 amino acids differs from KPC-2 by two insertions after positions 179 (ins179_TY) and 270 (ins270_DDKHSEA), respectively. Conjugation and cloning experiments confirmed that KPC-123 was able to confer high-level resistance to ceftazidime and ceftazidime/avibactam (MICs of 128 mg/L and 64/4 mg/L, respectively) and elevated MIC values of cefotaxime, cefepime, and aztreonam (4 mg/L, 2 mg/L, and 4 mg/L, respectively) but retained susceptibility to carbapenems. Whole-genome sequencing and genomic analysis revealed that blaKPC-123 within the “ISKpn27-blaKPC-ISKpn6” structure was located on an 93,814-bp conjugative plasmid which was almost identical to a blaKPC-2-carrying plasmid harbored in a K. pneumoniae isolate from the same sampling site of the patient, suggesting the transfer and in vivo evolution of this blaKPC-carrying plasmid. Hence, active surveillance of ceftazidime/avibactam resistance and the underlying mechanisms, which may facilitate the prevention and control of the dissemination of resistance, is needed.